El desarrollo conceptual de la ciencia cognitiva. Parte II* (2012)
INTRODUCTION: Cognitive science has become the most influential paradigm on mental health in the late 20(th) and the early 21(st) centuries. In few years, the concepts, problem approaches and solutions proper to this science have significantly changed.METHOD: Introduction and discussion of the fundamental concepts of cognitive science divided in four stages: Start, Classic Cognitivism, Connectionism, and Embodying / Enacting. The 2(nd) Part of the paper discusses the above mentioned fourth stage and explores the clinical setting, especially in terms of cognitive psychotherapy.DEVELOPMENT AND CONCLUSIONS: The embodying/enacting stage highlights the role of the body including a set of determined evolutionary movements which provide a way of thinking and exploring the world. The performance of cognitive tasks is considered as a process that uses environmental resources that enhances mental skills and deploys them beyond the domestic sphere of the brain. On the other hand, body and mind are embedded in the world, thus giving rise to cognition when interacting, a process known as enacting. There is a close connection between perception and action, hence the interest in real-time interactions with the world rather than abstract reasoning. Regarding clinics, specifically the cognitive therapy, there is little conceptual discussion maybe due to good results from practice that may led us to consider that theoretical foundations are firm and not problem-raising.